Crystal structure of 4,6-diamino-2-sulfanylidene-1,2-dihydropyridine-3-carbonitrile - Mohamed, Shaaban K. (International Union of Crystallography, 2014)
The title compound, C(6)H(6)N(4)S, crystallizes with two independent molecules, A and B, in the asymmetric unit. Both independent molecules are almost planar [maximum deviations of 0.068 (6) Å in molecule A and 0.079 (6) Å in molecule B]. In the crystal, molecules A and B are linked by N—H⋯S, N—H⋯N and C—H⋯S hydrogen bonds, forming a three-dimensional network.